Terminalia catappa Exerts Antimetastatic Effects on Hepatocellular Carcinoma through Transcriptional Inhibition of Matrix Metalloproteinase-9 by Modulating NF-κB and AP-1 Activity. (8th November 2012) - Yeh, Chao-Bin; Hsieh, Ming-Ju; Hsieh, Yih-Shou; Chien, Ming-Hsien; Lin, Pen-Yuan; Chiou, Hui-Ling; Yang, Shun-Fa
Abstract : High mortality and morbidity rates for hepatocellular carcinoma (HCC) in Taiwan primarily result from uncontrolled tumor metastasis. Previous studies have identified that Terminalia catappa leaf extracts (TCE) exert hepatoprotective, antioxidative, antiinflammatory, anticancer, and antimetastatic activities. However, the effects of TCE on HCC and the underlying molecular mechanisms of its activities have yet to be fully elucidated. The present study's findings demonstrate that TCE concentration dependently inhibits human HCC migration/invasion. Zymographic and western blot analyses revealed that TCE inhibited the activities and expression of matrix metalloproteinase-9 (MMP-9). Assessment of mRNA levels, using reverse transcriptase polymerase chain reaction (PCR) and real-time PCR, and promoter assays confirmed the inhibitory effects of TCE on MMP-9 expression in HCC cells. The inhibitory effects of TCE on MMP-9 proceeded by upregulating tissue inhibitor of metalloproteinase-1 (TIMP-1), as well as suppressing nuclear translocation and DNA binding activity of nuclear factor-kappa B (NF- κ B) and activating protein-1 (AP-1) on the MMP-9 promoter in Huh7 cells. In conclusion, TCE inhibits MMP-9 expression and HCC cell metastasis and, thus, has potential use as a chemopreventive agent. Its inhibitory effects are associated with downregulation of the binding activities of the transcription factors NF- κ B and AP-1. Corrigendum to " Terminalia catappa Exerts Antimetastatic Effects on Hepatocellular Carcinoma through Transcriptional Inhibition of Matrix Metalloproteinase-9 by Modulating NF- κ B and AP-1 Activity" dx.doi.org/10.1155/2015/326234